Meaningful Participation and Ecological Justice in Environmental Law: A Four-Jurisdiction Comparative Study - Rohmy, Atikah Mardhiya; Hassan, Hashem; Nihayaty, Arini Indah; Rachman, Rio Febriannur (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2026)
This article examines meaningful participation as a structural mechanism for advancing ecological justice in environmental and forest governance. Exclusionary governance has produced persistent inequalities for Indigenous and rural communities whose participation remains largely procedural. This study analyzes the gap between normative participatory commitments and their substantive implementation across four jurisdictions — Indonesia, New Zealand, the United Kingdom, and the European Union — using a qualitative Systematic Literature Review of peer-reviewed scholarship, legal instruments, and policy documents. Findings reveal significant institutional variation: Indonesia exhibits centralized authority and weak accountability; New Zealand institutionalizes ecological justice through the legal personhood of Te Urewera and the Whanganui River; the United Kingdom demonstrates procedural transparency without redistributive impact; the European Union provides multilevel participatory architecture with uneven equity outcomes. The study argues that meaningful participation requires structural guarantees of recognition, accountability, and empowerment — not procedural inclusion alone — and offers conceptual tools for reforming environmental law in contexts marked by power asymmetries and ecological degradation.